DRILLING THE UNDRILLABLE; A REVIEW OF INDONESIA ONSHORE MANAGED PRESSURE DRILLING (MPD) OPERATION EXPERIENCES - Ganesha R Darmawan; Aries Prasetyo (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2021)
MPD (Managed Pressure Drilling) has been used worldwide to overcome drilling challenges in onshore and offshore operations. MPD has proven to save significant cost efficiency in every applications, by reducing NPT (Non Productive Time) caused by drilling problems such as, severe loss circulations, loss-kick cycle, and well control events. Indonesia is one of major country in Asia Pacific that has several needs to developing or exploring new opportunities with drilling challenges, especially in vuggular carbonate reservoirs, narrow drilling windows, and wellbore in-stability. This paper will present the basic theory on MPD, MPD equipment’s, types of MPD, and elaborate more on successful MPD operation in onshore Indonesia, and clustering the solutions of drilling challenges.